Projection of Paddy Production in Kedah Malaysia: A Case Study - Md Yusof, Zahayu; Misiran, Masnita; Baharin, Nur Fatiha; Yaacob, Mohammad Fahmi; Abdul Aziz, Nur Athirah; Sanan, Nur Hanani (2019)
Rice is a staple food for Malaysian. Malaysian paddy farmers contributed up to 70% of the country’s needs. However, climate change impact to the agriculture activities. The aim of this study is to forecast the paddy production for four years in Kedah, Malaysia. Naïve forecasting method was used in this study. The forecasted results for the paddy production values from 2013 to 2016 are considered in this study. The finding shows that the decrease of paddy production in the year of 2013 but the paddy production increased from year 2014 until 2016. Overall, this research work forecasted gradual increments for the projection of four years rice’s production in Kedah